2006
DOI: 10.1002/em.20210
|View full text |Cite
|
Sign up to set email alerts
|

In vivo genotoxic effects of industrial waste leachates in mice following oral exposure

Abstract: Contamination of ground water by industrial waste poses potential health hazards for man and his environment. The improper disposal of toxic wastes could allow genotoxic chemicals to percolate into ground waters, and these contaminated ground waters may produce toxicity, including mutation and eventually cancer, in exposed individuals. In the present study, we evaluated the in vivo genotoxic potential of leachates made from three different kinds of industrial waste (tannery waste, metal-based waste, and waste … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Several studies have suggested that mutagenic agents produce carcinogenic effects (Chandra et al, 2006). The combined use of the comet Assay and micronucleus test in a single study has yielded good results.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have suggested that mutagenic agents produce carcinogenic effects (Chandra et al, 2006). The combined use of the comet Assay and micronucleus test in a single study has yielded good results.…”
Section: Discussionmentioning
confidence: 97%
“…This assay is an in vivo short-term test developed by Heddle (1973) and Schmid (1975) and it is useful to investigate compounds with clastogenic (leading to chromosome breakage) and aneugenic (resulting in chromosome loss) activities (Schmid, 1975;Hayashi et al, 1990). Studies have already demonstrated that many mutagenic components exhibit carcinogenic effects (Chandra et al, 2006;Suzuki et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Aquatic animal assay using goldfish (Carassius auratus) also indicates that raw landfill leachate induced DNA damage in peripheral erythrocytes, and increased the frequency of micronucleus (MN) in gill cells [4]. Investigation on mammals shows that both municipal landfill leachate and industrial solid waste leachate could cause the increase of MN and chromosomal aberration (CA) frequency, and contribute to the formation of DNA damage in mouse bone marrow and blood cells in vivo [5][6][7], and may be responsible for the DNA damage in human peripheral blood lymphocytes [8]. The cytogenetic abnormalities and DNA damage induced by landfill leachate implicate that humans consuming leachate contaminated water are at increased risk of developing adverse health consequences.…”
Section: Introductionmentioning
confidence: 97%